1999
DOI: 10.1016/s0896-6273(00)80813-2
|View full text |Cite
|
Sign up to set email alerts
|

Specific Involvement of PKC-ε in Sensitization of the Neuronal Response to Painful Heat

Abstract: Pain is unique among sensations in that the perceived intensity increases, or sensitizes, during exposure to a strong stimulus. One important mediator of sensitization is bradykinin (BK), a peptide released as a consequence of tissue damage. BK enhances the membrane ionic current activated by heat in nociceptive neurons, using a pathway that involves activation of protein kinase C (PKC). We find that five PKC isoforms are present in sensory neurons but that only PKC-epsilon is translocated to the cell membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
375
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 387 publications
(405 citation statements)
references
References 36 publications
28
375
1
1
Order By: Relevance
“…TRPV1 is acknowledged to exist in peripheral nerve terminals and can be sensitized by noxious heat over 43 °C. Additionally, some evidence also validates the contribution of TRPV1 to mechanotransmission after injuries in different conditions [42][43][44] .…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…TRPV1 is acknowledged to exist in peripheral nerve terminals and can be sensitized by noxious heat over 43 °C. Additionally, some evidence also validates the contribution of TRPV1 to mechanotransmission after injuries in different conditions [42][43][44] .…”
Section: Discussionmentioning
confidence: 61%
“…The function of TRPV1 is augmented by many endogenous mediators following direct PKCε activation [15] . Specifically, the phosphorylation and activation of PKCε intensifies the responses of sensory neurons to noxious heat [16] . Previous studies have demonstrated that PKCε activation in small-and medium-sized DRG neurons alters the TRPV1 function and consequently leads to hyperalgesia.…”
Section: Original Articlementioning
confidence: 99%
“…UTP activates the P2Y purinergic GPCR, which is also coupled to PKC-. PKC-induces sensitization of nociceptors via changes in TRPV1 (Cesare et al, 1999) and contributes to inflammatory hyperalgesia (Hucho et al, 2005). PKC activators increase TTXr-Per current in rat and mouse DRG neurons (Baker, 2005) so that its sensitizing actions are likely to be attributable to changes in TRP and voltage-gated sodium channels.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory mediators, including amines, prostanoids, kinins, purines, protons, and nerve growth factor (NGF), sensitize the nociceptor peripheral terminal by producing a reduction in the threshold of transducer channels (McCleskey and Gold, 1999;Julius and Basbaum, 2001), an increase in terminal membrane excitability (Amir et al, 2006), and insertion of receptors into the terminal membrane (Zhang et al, 2005). The high threshold of the transducers are reduced by posttranslational processing in response to activation by the inflammatory mediators of multiple intracellular signaling pathways [PKA, PKC, extracellular signalregulated kinase, phosphatidylinositol 3 (PI3) kinase, and phospholipase C] (Cesare et al, 1999;Aley et al, 2001;Bautista et al, 2006). Prostaglandin E 2 (PGE 2 ), 5-HT, and bradykinin (BK) increase the Na v 1.8-like TTXr current in DRG neurons, with an increase in amplitude and rates of activation and inactivation (Gold et al, 1996(Gold et al, , 1998England et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…PKD, together with PKCε, can phosphorylate the transient receptor potential/vanilloid channel of nociceptive neurons, resulting in hyperalgesia to thermal stimuli (5,53). A similar role of PKD in controlling IPAN excitability is of particular interest, since this kinase is capable of sustained activation and of amplifying receptor-mediated signals (26).…”
mentioning
confidence: 99%